Hemifacial Microsomia - A Case Report - Sushma Rao; K S Nagesh; Asha Iyengar; Jyothi Gupta (Wolters Kluwer Medknow Publications, 2005)
Hemifacial Microsomia is a disorder characterised by the anomalies of the face, ears, eyes and the vertebrae. The incidence of this disorder is 1:3000 to 26, 000 and is usually seen at birth. It may be familial or sporadic cases. The disorder is more common in males especially on the right side of the face. The disorder was first identified by M. Goldenhar and J. Genet Hum in 1952, and was called Oculo-Auriculo-Vertebral dysplasia by R. J. Gorlin. Clinically one sees facial asymmetry, macrostomia, micrognathia, and microtia to anotia of the external ear, preauricular skin tags, and Epibulbar tumors in the eyes. One such case of Hemifacial Microsomia seen in a boyaged 9 years, who complained of facial asymmetry on the right side of the face since birth and an extra auricle on the same side, is reported here.